COMPARATIVE SOUNDNESS OF COMMERCIAL BANKS STATE-OWNED AND NATIONAL PRIVATE BANKS BASED ON RBBR - Rd Ayu Puspitarini; Nunung Aini Rahmah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The soundness of banks is a critical issue to research because they serve as the backbone of a nation's economy. A bank's success in adhering to applicable regulations, executing risk management, and following the precautionary principle can be assessed by measuring the soundness level of the bank. The purpose of this study is to determine how, using the RBBR approach, the soundness levels of state-owned and national private commercial banks differ, as measured by four indicators: Risk Profile, GCG, Earnings, and Capital for the years 2018–2022. Purposive sampling was used to choose the research sample. This research was conducted by analyzing the Mann-Whitney U Test. The analysis results show that in the 2018-2022 period, there is a significant difference between the soundness of state-owned conventional commercial banks and national private conventional commercial banks in the Capital aspect. Besides, there are no significant differences in the elements of Risk Profile, GCG, and Earnings. It is hoped that this research can help bank management evaluate the implementation of risk management, GCG principles, earnings, and capital so that they can continue to compete with other bank groups.